Assessment of Brain Derived Neurotrophic Factor in hair to study stress responses: A pilot investigation. (December 2017) - Harb, H.; González-de-la-Vara, M.; Thalheimer, L.; Klein, U.; Renz, H.; Rose, M.; Kruse, J.; Potaczek, D.P.; Peters, E.M.J.
Highlights: BDNF in hair negatively correlates with hair-cortisol and somatic complaints (SC). H4 histone acetylation at the BDNF gene P4-promoter negatively correlates with SC. Students with high SC during the end of term exam have lower hair-BDNF. Therefore, BDNF protein levels can be determined in clipped hair. Also, cells from plucked hair can be used for epigenetic analysis of stress-effects. Abstract: To study pathogenic stress-effects in health and disease, it is paramount to define easy access parameters for non-invasive analysis of biological change in response to stress. Hair samples successfully provide this access for the study of hypothalamus-pituitary-adrenal axis (HPA) changes. In this study, we assess the hair expression and corresponding epigenetic changes of a neurotrophin essential for autonomic nervous system function and mental health: brain derived neurotrophic factor (BDNF). In three independent studies in healthy academic volunteers (study I: German students, N = 36; study II, German academic population sample, N = 28; study III: Mexican students, N = 115), BDNF protein expression or BDNF gene ( BDNF ) histone acetylation was determined. Simultaneously, mental distress and distress-associated somatic complaints were assessed by self-report. In study I, we found a negative correlation between hair-BDNF protein level and hair-cortisol as well as between hair-BDNF and somatic complaints, while hair-cortisol correlated positively with mental distress. In study II, we found a negative correlation between H4 histone acetylation at the BDNF gene P4-promoter and somatic complaints. Regression analysis confirmed confounder stability of associations in both studies. In study III, we confirmed study I and found lower hair-BDNF protein level in volunteers with high somatic complaints, who also reported higher mental distress during the end of term exams. The results indicate that BDNF protein levels can be detected in clipped hair and are associated with somatic complaints and stress in life. In addition, we concluded that plucked hair can provide material for the study of epigenetic changes in stress-affected tissues. These tools can prove valuable for future studies on distress, both under experimental and field conditions.